Hypertonic saline test for the investigation of posterior pituitary function. Issue 5 (1st November 1998) - Mohn, Angelika; Acerini, Carlo L; Cheetham, Timothy D; Lightman, Stafford L; Dunger, David B
Abstract : The hypertonic saline test is a useful technique for distinguishing partial diabetes insipidus from psychogenic polydipsia, and for the diagnosis of complex disorders of osmoreceptor and posterior pituitary function. However, there is little information concerning its use in childhood. The experience of using this test in five children (11 months to 18 years) who presented diagnostic problems is reported. In two patients, in whom water deprivation tests were equivocal or impractical, an inappropriately low antidiuretic hormone (ADH) concentration (< 1 pmol/l) was demonstrated in the presence of an adequate osmotic stimulus (plasma osmolality > 295 mosmol/kg). In two children—one presenting with adipsic hypernatraemia and the other with hyponatraemia complicating desmopressin treatment of partial diabetes insipidus—defects of osmoreceptor function were identified. Confirming a diagnosis of idiopathic syndrome of inappropriate ADH secretion (SIADH) was possible in a patient with no other evidence of pituitary dysfunction. The hypertonic saline test was well tolerated, easy to perform, and diagnostic in all cases.